1984
DOI: 10.2135/cropsci1984.0011183x002400030009x
|View full text |Cite
|
Sign up to set email alerts
|

Production of 2n Pollen in Red Clover1

Abstract: The success of tetraploid red clover (Trifolium pratense L.) in Europe has stimulated interest in developing tetraploid red clover adapted to the United States. The use of 2n gametes to produce tetraploid alfalfa (Medicago sativa L.) and potato (Solanum tuberosum L.) from diploid germplasm suggests that 2n gametes may be an alternative to chemical treatment. Diploid plants that produce 2n eggs are known to occur in red clover, and plants that produce 2n pollen have been reported. The objectives of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 0 publications
1
34
1
1
Order By: Relevance
“…Other authors also reported variable GP production, ranging from 4 to 37% in alfalfa (McCoy, 1982), and from 1 to 11% in Lotus tenuis (Negri, 1992). In this study, the range of variation in GP production in the initial population (0 to 9.07%) was lower than those values cited above, but the percentage of individuals producing more than 1% GP (19.91%) was remarkably higher in comparison to the red clover population studied by Parrott & Smith (1984). In this species, 2n pollen is formed due to the occurrence of parallel or tripolar spindles during anaphase II (Parrot & Smith, 1984).…”
Section: F 3 Generationcontrasting
confidence: 49%
See 3 more Smart Citations
“…Other authors also reported variable GP production, ranging from 4 to 37% in alfalfa (McCoy, 1982), and from 1 to 11% in Lotus tenuis (Negri, 1992). In this study, the range of variation in GP production in the initial population (0 to 9.07%) was lower than those values cited above, but the percentage of individuals producing more than 1% GP (19.91%) was remarkably higher in comparison to the red clover population studied by Parrott & Smith (1984). In this species, 2n pollen is formed due to the occurrence of parallel or tripolar spindles during anaphase II (Parrot & Smith, 1984).…”
Section: F 3 Generationcontrasting
confidence: 49%
“…Frequency of unreduced gametes production in non-hybrid plants is generally less than 1%, and may vary among individuals (Veilleux, 1985;Ramsey & Schemske, 1998, Lyrene et al, 2003. In the work of Parrott & Smith (1984) for instance, 3% of the diploid red clover plants analyzed produced more than 1% GP (reaching up to 84% GP). Other authors also reported variable GP production, ranging from 4 to 37% in alfalfa (McCoy, 1982), and from 1 to 11% in Lotus tenuis (Negri, 1992).…”
Section: F 3 Generationmentioning
confidence: 97%
See 2 more Smart Citations
“…Numerous mutants result in the formation of unreduced gametes in flowering plants (2n gametes ;Hermsen 1984;Veilleux 1985;Parrott and Smith 1986;D'Amato 1989;Bretagnolle and Thompson 1995). Many exhibit high sex specificity, suggesting genetic divergence between mechanisms controlling unreduced pollen and unreduced egg cell formation (Veronesi et al 1986;Werner and Peloquin 1989;De Haan et al 1992).…”
Section: Reproductive Versatility In Flowering Plantsmentioning
confidence: 99%